Methodology and implementation of the WHO European Childhood Obesity Surveillance Initiative (COSI). (4th November 2021) - Breda, João; McColl, Karen; Buoncristiano, Marta; Williams, Julianne; Abdrakhmanova, Shynar; Abdurrahmonova, Zulfiya; Ahrens, Wolfgang; Akhmedova, Dilorom; Bakacs, Márta; Boer, Jolanda M.A.; Boymatova, Khadichamo; Brinduse, Lacramioara Aurelia; et al.
Summary: Establishment of the WHO European Childhood Obesity Surveillance Initiative (COSI) has resulted in a surveillance system which provides regular, reliable, timely, and accurate data on children's weight status—through standardized measurement of bodyweight and height—in the WHO European Region. Additional data on dietary intake, physical activity, sedentary behavior, family background, and school environments are collected in several countries. In total, 45 countries in the European Region have participated in COSI. The first five data collection rounds, between 2007 and 2021, yielded measured anthropometric data on over 1.3 million children. In COSI, data are collected according to a common protocol, using standardized instruments and procedures. The systematic collection and analysis of these data enables intercountry comparisons and reveals differences in the prevalence of childhood thinness, overweight, normal weight, and obesity between and within populations. Furthermore, it facilitates investigation of the relationship between overweight, obesity, and potential risk or protective factors and improves the understanding of the development of overweight and obesity in European primary‐school children in order to support appropriate and effective policy responses.